Modelling the Demand of Fresh Meat by Households in Malaysia - Nordiana Marjan Rusli; Assis Kamu (2020)
There have been some changes in Malaysians’ food preference as Malaysia is one of the most developing countries in Asia. These changes in consumption pattern have some impact on the agriculturally based food industry. One of the changes is in the preference for fresh meat such as poultry, beef, mutton, and other meat. This study is focusing on demand elasticity of fresh meat by households in Malaysia. This study has obtained demand elasticity of fresh meat via Linear Approximate Almost Ideal Demand System (LA-AIDS). Data from the Household Expenditure Survey (HES) 2014 has been used to build a statistical model in estimating the demand elasticity.